Importance of operational management to achieve sustaintability in a smb - Pérez Astorga, Steffy; Olvera Muñoz, Martín Alejandro; Reynosa Barbosa, Angélica (UANL. Facultad de Contaduría Publica y Administración, 2014)
This paper shows a study we made to benefit small companies in general, it based in the problems that a SMB had in the last years (CIEM). We examine the problems or situations that have played a big role in CIEM’s decrease in production and try to provide solutions for each of the problems and provide a general solution for the enterprise that could help to increase its profit, hoping these also help many other small companies going through the same kind of problems.